Produção e caracterização de anticorpos monoclonais contra a região idêntica das proteínas LigA e LigB de Leptospira interrogans - Monte, Leonardo Garcia (2009)
Leptospirosis is a zoonotic disease caused by pathogenic bacteria belonging to the Leptospira genus. Several mammals may carry the agent, and rats are the most important source of human infection in urban settings. The wide spectrum of clinical manifestations varies from mild cases, with fever and headaches, to severe presentations, with liver and kidney failure, which may lead to death. As a result of the various degrees of severity, leptospirosis is frequently mistaken, in its acute stage, with other tropical diseases such as influenza and dengue. The microscopic agglutination test (MAT) is considered the gold standard when diagnosing leptospirosis; however, the test presents limitations regarding sensitivity in the acute phase of the disease. Recently, surface proteins LigA and LigB have been identified to be related with leptospiral virulence. These proteins have been characterized as adhesins, with a proteic structure similar to Escherichia coli intimin and Yersinia pseudotuberculosis invasin, which are important virulence factors in these organisms. The goal of this study was to produce and characterize monoclonal antibodies (MAbs) against a truncated fragment of approximately 54 kDa, named rLigBrep, that comprise a identical portion of LigA and LigB (domains 2-7). The 5 MAbs obtained were of the IgG1 (2) and IgG2b (3) isotypes and their affinity constants for rLigBrep varied from 7 x 107 M-1 to 4 x 108 M-1. The MAbs were able to react with the native antigen in L. interrogans serovar Copenhageni strain Fiocruz L1-130 by indirect immunofluorescence, immunoblotting, whole-cell ELISA and immunoelectron microscopy. These results allow concluding that these MAbs are important tools for studies aiming understanding the role of Lig proteins in Leptospira pathogenesis and in the development of tests for diagnosis of leptospirosis.